Length functions in Teichmüller and anti-de Sitter geometry - Filippo Mazzoli; Gabriele Viaggi (Forum of Mathematics, Sigma, 2023)
We establish a link between the behavior of length functions on Teichmüller space and the geometry of certain anti-de Sitter